Efficacy of high-intensity interval training compared with moderate-intensity continuous training on maximal aerobic potency in dogs: Trial protocol for a randomised controlled clinical study (2021)
Background: High-intensity interval training (HIIT) is a more efficient method to improve exercise capacity than moderate-intensity continuous training (MICT) because of its greater physiological stimulus. Objective: The aim of this protocol is to evaluate the efficacy of HIIT on maximal aerobic potency in dogs as compared to MICT. Methods: This protocol is for a randomised, blinded controlled clinical trial, with three parallel groups for the purpose of demonstrating superiority. Thirty dogs aged between 12 and 84 months of both sexes and different breeds will be included. Dogs, before initiating and after finalising the training will perform an incremental exercise test on a treadmill to obtain maximal speed and lactate threshold; resting parameters of heart and respiratory rate, left ventricle chamber and systolic function will be measured. Dogs assigned to each intervention will endure a 42-min session of HIIT or MICT during 12 weeks. HIIT comprises four intervals of 4 min each at a load of 85%, alternating with a 4-min resting period. MICT group will have a continuous load of 60%. The control group will remain in a cage. An intention-to-treat statistical analysis will be implemented. Analysis of covariance will be used to estimate the effect of HIIT compared with MICT training on maximal aerobic potency, aerobic resistance, systolic function at rest, left ventricle chamber measurements and indexes, respiratory rate and HR at rest. Conclusion: Significant time and effort are invested into training sports/working dogs, which could benefit from improving physical capacity by means of the HIIT methodology.